Medical Management of Aortic Disease: If They Don’t Need Surgery, What Do They Need? - Mujtaba Saeed; Maan Malahfji (Methodist DeBakey Cardiovascular Journal)
Management of aortic disease has evolved significantly over the past few decades. A preemptive diagnostic approach with a multidisciplinary team and shared decision-making has led to improved clinical outcomes. Surgery is the cornerstone of management for most aortic conditions; however, medical therapy is now an important adjunctive therapy in most if not all patients. Herein, we review the role and evidence behind medical management of patients with aortic disease.